Quality service performance model in academic library: a case study at research University (USM) / Junaida Ismail ... [et al.] - Ismail, Junaida; Ladisma@ Awis, Mahadir; Musa Sharunizam Shari, Aishah; Abu, Roziya (2009)
This study in particular scrutinizes the quality service in academic library. The reason for choosing academic libraries at Research University (USM) is because this university by virtue provides service par excellence. Thus, the implementation of quality service could be a guideline or standards to others. The objectives of this study are i) to determine whether there exits a relationship between the five dimensions and the service quality of an academic library at Research University (USM); ii) to determine the elements in each dimension that contributed to the service performance of an academic library at Research University (USM) and ill) to evaluate the most dominant dimension that influences the services quality performance in an academic library at the research University (USM). This study will employ the basic SERVQUAL model by Parasuraman (1996). Five determinant of quality service has been pre-identified which are Library as a Place (Tangible), Collections, Access, Reliability and Empathy. The sampling technique that had been used in this research was the Stratified Random Sampling. There are 377 respondents of academic libraries at research university (USM) involved. A set of questionnaire were developed to collect the data. The findings of this study may give a useful insight to the quality services provided to the user.